Quantitative determination of trace organic polutants in municipal sewage sludge - Ahmad, Umi Kalthom (Universiti Teknologi Malaysia, 2006)
In this study, a supercritical fluid CO2 (SF-CO2) extraction and subcritical water extraction (SWE) were developed with the aim of overcoming the disadvantages associated with the conventional soxhlet extraction. The SFE conditions utilised extraction temperature of 60 oC, extraction pressure of 200 bar, 15% methanol as cosolvent, extraction flow rate at 2.0 mL/min, 30 minute extraction and n-hexane as the analyte trapping solvent for PCBs extraction from sludge. A lab-made SWE dynamic extraction system was successfully developed for the dynamic SWE of PCBs from sludge samples. For the SWE, the optimized conditions employed an extraction temperature of 250 oC, extraction pressure of 50 bar, 1 min static followed by 10 min dynamic extraction and analyte collection in dichloromethane. Both the SF-CO2 extraction and SWE showed good PCB recoveries (50 to 99 %) compared to soxhlet extraction (52 to 75 % PCB recoveries). From the two extraction methods investigated, it was clear that the SF-CO2 technique was better in terms of recovery, good reproducibility and speed of analysis compared to the SWE method and it was therefore chosen as the method of choice for the analysis of real sludge samples. The PCBs under study (PCB 28, 52, 101, 118, 138, 153 and 180) when analysed using GC-ECD gave low detection limits in the range of 0.016 to 0.048 µg/mL. The concentration of PCBs in sludge samples extracted using SF-CO2 were in the range of 31.2 to 82.0 µg/kg as compared to that using soxhlet with PCB levels from 20.2 to 60.1 µg/kg. Method development for analysis of PAHs in sewage sludge was also carried out using spiked samples and real samples. Extraction of PAHs in sewage sludge was utilised using Soxhlet extraction followed by extract clean-up procedure. Limits of detection for five PAHs (naphthalene, fluoroanthene, phenanthrene, benzo(a)fluoroanthene and benzo(a)pyrene) were in the range of 5 mg/L to 20 mg/L. Analysis of OCP (lindane,dieldrin, TDE, pp-DDT and heptachlor) in sewage sludge was also successfully developed. The use of GC-ECD instrument was successful in separating and detecting all OCPs under study. In this study, limits of detection of OCP were in the range of 7.8 to 39.0 µg/kg. Extracts of OCP in sewage sludge were prepared using Soxhlet extraction followed by clean-up procedure using silica column. The concentrations of OCPs were in the range of (47 to 159 µg/kg) in sewage sludge. The characterization of sludge samples from other aspects was also carried out. The sludge samples showed high water content (37 to 90 %) with slightly acidic pH values ranging from 4.3 to 6.6. All samples were found to be chemically stable and the percentages of nutrient (TKN, P and K) were in the range of 0.059 to 0.98 %, 0.05 to 0.15 % and 0.12 to 0.16 %, respectively. Heavy metal studies showed that metal content in municipal sewage sludge samples were below the USEPA limit.